Design and synthesis of structurally well-defined functional polyolefins via transition metal-mediated olefin polymerization chemistry - Dong, Jin-Yong; Hu, Youliang (Coordination chemistry reviews, 2006)
The functionalization of polyolefins has long been an industrially important yet scientifically challenging research subject ever since the commercialization of polyethylene (PE) and polypropylene (PP) in the 1950s. However, only until recently has considerable progress been made thanks to the enormous development of transition metal olefin polymerization catalysis (Ziegler-Natta, metallocene and post-metallocene). This review covers recent achievements in the functionalization of polyolefins, with special attention being paid to the chemistries using transition metal-catalyzed process to synthesize structurally well-defined functional polyolefins, including side group-functionalized polyolefins, chain end-functionalized polyolefins and functional polyolefins with graft and block structures.